Generator analysis and comparison of working fluids in the organic Rankine cycle for biomass power plants using Aspen Plus software - Siregar, Yulianta; Sihotang, Wahyu Franciscus; Mohamed, Nur Nabila (Institute of Advanced Engineering and Science, 2025)
The organic Rankine cycle utilizes low-temperature heat (flue heat) in power plants to produce electrical power. Several factors, including the working fluid's temperature and pressure, influence the efficiency of an organic Rankine cycle. This research method includes calculations using the gasification method in calculating electrical energy in PLTBM and calculating the experimental results of a series of organic Rankine cycles by taking into account the temperature and pressure of the working fluid using Aspen Plus Software, which is analyzed using statistical methods. The results of research using the gasification method in PLTBM fuel produced power of 27,279.38 MW/year for coconut shells, 6,489.66 MW/year for rice husks, and 532.62 MW/year for corn cobs. For the organic Rankine cycle series, rice husk waste produces the largest power of 8,336.67 kW, for coconut shells of 569,723.95 kW. For corn cobs of 358,639.63 with an efficiency value of organic working fluid in R-22 of 25.37% and the R-32 organic working fluid of 11.92% at a temperature of 125 °C in coconut shell waste, it can be concluded that the temperature of the working fluid has more influence on the efficiency of the organic Rankine cycle than the pressure of the working fluid.